2019
DOI: 10.1073/pnas.1904318116
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain metabolic activity: Beyond the concept of brain age

Abstract: We have read the article in PNAS by Goyal et al. (1) with great interest. The identification of underlying organic differences between female and male brains is of utmost importance to reach sex-sensitive precision medicine (2)(3)(4).The main findings of the paper (1), "the female brain has a persistently lower metabolic brain age-relative to their chronological age-compared with the male brain," lend themselves to the conclusion that women's brains are younger than men's. However, we would like to raise a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Brain glucose metabolism can be visualized with brain imaging techniques at the level of brain structure, neuronal activity, and functional circuitry (59). Leveraging multitracer position-emission tomography (PET) scans of >200 cognitively normal individuals, aerobic glycolysis, estimated by the difference between total glucose use and oxygen consumption, was found to be higher in female brain as compared with males of the same age (26,60,61). Oxygen consumption can be contributed by other metabolic inputs of the tricarboxylic acid cycle such as glutamate and lipid, and thus it is important to note that alternative or complementary interpretations of this result is possible such as sex bias in mitochondrial fuel selection.…”
Section: Metabolic Sex Dimorphism In Brain Tissue Microenvironmentmentioning
confidence: 99%
“…Brain glucose metabolism can be visualized with brain imaging techniques at the level of brain structure, neuronal activity, and functional circuitry (59). Leveraging multitracer position-emission tomography (PET) scans of >200 cognitively normal individuals, aerobic glycolysis, estimated by the difference between total glucose use and oxygen consumption, was found to be higher in female brain as compared with males of the same age (26,60,61). Oxygen consumption can be contributed by other metabolic inputs of the tricarboxylic acid cycle such as glutamate and lipid, and thus it is important to note that alternative or complementary interpretations of this result is possible such as sex bias in mitochondrial fuel selection.…”
Section: Metabolic Sex Dimorphism In Brain Tissue Microenvironmentmentioning
confidence: 99%
“…We ran three age prediction models: 1) mixed-sex, 2) female only, and 3) male only, to obtain sex-specific BAG values [53,95] as well as general BAG estimates based on the mixed sample.…”
Section: Brain Age Predictionmentioning
confidence: 99%
“…While DTI is commonly used to estimate WM indices that are highly sensitive to age [73,86,87,88], biophysical diffusion models such as WMTI [85], which is derived from DKI [84], may more accurately capture WM tissue structure complexity [84,89], thus providing greater biological specificity [90]. Given previous work indicating structural and functional sex differences in the human brain [91,92,93,94], the diffusion metrics were used as input features to three separate prediction models; 1) mixed-sex, 2) female only, and 3) male only, in order to improve the accuracy of the sex-specific analyses [53,95,96]. We used linear regression models to assess whether associations between BAG and BMI, WHR, BF%, and APOE genotype varied i) between males and females, ii) according to age at menopause in females, and iii) across different age groups in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the longer life expectancy of women has been ascribed to biological factors as well as genderspecific lifestyle attitudes [29]. Biologically, for instance, recent studies report that women have younger brains in terms of metabolic activity than men [30,31]. Further, men of certain ages appear to be more vulnerable to death by cardiovascular events, as the Framingham's heart study showed higher midlife cardiovascular mortality in men than in women [19].…”
Section: Agementioning
confidence: 99%